The effects of intravenous L-dopa on plasma renin activity, renal function, and blood pressure in man - Worth, D; Harvey, J; Brown, J; Lee, M (European journal of clinical pharmacology, 1988)
L-dopa 7 micrograms.kg-1.min-1 was given intravenously over 2 h to six healthy subjects, controlled by an infusion of saline on a separate occasion, with measurement of plasma renin activity (PRA), urinary sodium and potassium excretion, effective renal plasma flow (ERPF), glomerular filtration rate (GFR), blood pressure, and pulse rate. Mean PRA fell by 50% following L-dopa, which was significantly different from the slight rise which occurred after saline infusion. There was a significant increase in urinary sodium excretion and effective renal plasma flow on infusion of L-dopa. Mean diastolic blood pressure fell during L-dopa infusion, in contrast to the slight increase which occurred during the control study. These observations confirm the anticipated renal dopaminergic effects of L-dopa and also suggest a dopaminergic influence on renin release in man.